STRATEGI PEMASARAN PRODUK BANK SYARIAH - Putri, Mistika Dina; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
This research is motivated by the relatively rapid growth of Islamic banking and has a positive effect on the professionalism of each institution, to increase market share and attract as many customers as possible. The goal according to marketing itself is to improve the quality of the product, increase sales, inform about new products. This research method is a qualitative method using the origin of the data, namely secondary data, then the type of research is in the form of literature review, then the data collection technique used is looking for correlated literature or using the core research discussion in the form of books and scientific journals, and analysis. The data used is descriptive where the collected data is described, then analyzed and conclusions drawn from the analysis carried out. The results according to the discussion are, for example, what we see. In this current era, the strategy in marketing products must be more adaptable, especially to the millennial community. Today's society cannot be separated from the digital world and social media, almost all of its activities involve digital. Therefore, the tactics and concepts applied in increasing public interest must also continue to be developed so that all levels of society can get to know the products offered more easily